On the eigenfunction expansions of the dyadic green's functions for multilayered biisotropic and bianisotropic media - Tan, Eng Leong. (2008)
This thesis contains a concise and unified analysis of electromagnetic wave propagation, scattering and radiation in multilayered complex media using dyadic Green's functions. The eigenfunction expansions of various dyadic Green's functions are formulated for biisotropic media in three canonical coordinate systems, general bianisotropic media in Cartesian coordinate system and gyrotropic bianisotropic media in cylindrical coordinate system. Many new, generalized, unified and/or condensed fundamental results are derived employing simple and direct means. In particular, a simple approach based on the theory of distributions is presented for deriving the singularities and discontinuities associated with the eigenfunction expansions of the dyadic Green's functions for biisotropic media.